Configuring the Mindanao Peace Process Implications for Development and Globalization - V. MAGDALENA, FEDERICO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper has two aims: (1) explore the ongoing Mindanao peace process involving, as major actors, the Moro Islamic Liberation Front (MILF) and the Philippine government to resolve the sovereignty-based conflict in the south, and (2) discuss some implications for development and constructing a Bangsamoro homeland, in the sense of a nation (or state) emerging, with its own diversity that encompasses various ethnic groups and identities. The paper contends that the peace process is also a cultural issue, besides its obvious political connotation. Hence, this process needs to be framed along the lines of culturalism - moving toward the direction of a multicultural mix sensitive to all ethnicities and respectful of cultural differences - foreground by globalization. Peace and stability are necessary conditions for development, especially so for new nations that confront, and are in turn influenced by the larger global processes. In particular, it proposes that the peace process cover certain grounds for dialogue and offers-some policy suggestions toward ending the conflict that has deeply divided Muslim and Christians, and marginalized other indigenous people (Lumads) in the Philippines. It is necessary to develop a "culture of peace" in this formulated homeland tuned in to globalization, both as space shared by diverse ethnic groups who enjoy equity and as locus where they can affirm their status and identity.